Disparity Regulation of Criminal Sanction Between Bribery Article 5 Section (2) and Gratification Article 12B Act Number 20 Year 2001 About Corruption Criminal Action - Dwi Winarto (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
Key Words: The Disparity or Comparison of Law means to describe the similarity and the difference between law systems or to look for the essence of similarity of whole law systems. Criminal Sanction, or usually known as criminal law, or sometimes just called as criminal, is an unpleasant feeling (misery) charged by the judge by giving verdict against the people who violate criminal law act. Bribery is giving or promising something to civil servant or state caretaker in order to make this civil servant or state caretaker to do something or not to do something with their rank but it may stand in violating against their duty. Gratification is the giving in wider sense of definition which involves money, goods, discount, commission, loan with no interest, traveler check, overnight facility, tourism journey, free medication, and other facilities. Gratification may be received within the host country or the foreign country, and can be given by electronic or by manual. Civil servant is the employee who has met the qualification, been appointed by the incumbent officer, given assignment of an official rank, or given other kinds of state duty, and paid with salary based in the regulation. State Caretaker is the state officer who implements the function of executive, legislative or judicative, or who works based on the function and principal task related to the organizing of state in pursuance of the regulation.